Analysis of Fuel Tank Collision Structure Based on Defense Point Method - Wenguang Liu; Haijiang Liu; Lin Jiang; Shanshan Bi (Journal of Advanced Transportation)
Aiming at the impact process of a fuel tank, which is a transient energy conversion process, the material absorbs energy through deformation to analyze the mechanical properties of the fuel tank during the impact process. The defense node method is adopted to simulate the dynamic response of the fuel tank during impact. The results show that it can accurately evaluate the safety of the container.